Celiac disease - a review on recent advances in characteristics, diagnostic and treatments - Artykiewicz, Klaudia; Czarkowski, Marcin; Gorczyca, Kamila; Grodkiewicz, Maria; Kozieł, Paweł; Krzysiek, Urszula; Podgórska, Klaudia; Puła, Aleksandra; Słupczyńska, Aleksandra; Urbaś, Weronika (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Celiac disease occurs in 1% of the general population. However, many cases remain unrecognized. The disease is a chronic immune-mediated disorder triggered by the ingestion of gluten that appears in individuals with genetic susceptibility. Celiac disease can develop in paediatric patients as well as adults. The purpose of this review is to analyze the newest information on the characteristics, diagnosis and treatment of patients with celiac disease. Material and methods: This review was based on available data collected in the PubMed database and published between 2015 and 2022. The research was done by looking through keywords such as: “celiac disease”, “Gluten-Free Diet”, “diagnosis” and “treatment”. Results: The diagnosis of celiac disease is most often delayed due to the broad spectrum of presentations. Screening of at-risk individuals is important to progress the diagnosis. It is additionally crucial to raise clinicians’ attention to non-specific parenteral symptoms that may indicate celiac disease. The majority of the symptoms arise from nutritional deficiencies caused by intestinal malabsorption. According to scientific reports, the most common deficiencies of people with celiac disease are iron, folic acid, vitamin B12, fat-soluble vitamins and a calcium. Conclusions: Recent years have seen the emergence of research into new therapeutic options, but their efficacy and safety still need to be evaluated more thoroughly. Strict adherence to a gluten-free diet by patients is still the only treatment option at present. Celiac disease, due to the constant increase in knowledge about its pathogenesis, diagnosis and treatment is an important material for further research.